1993
DOI: 10.1161/01.hyp.21.6.921
|View full text |Cite
|
Sign up to set email alerts
|

Captopril inhibits endothelin-1 secretion from endothelial cells through bradykinin.

Abstract: ET-1 induces a strong and sustained pressor response in vessels 1 and systemic hypertension in the rat.2 It also stimulates mitogenesis in vascular smooth muscle cells.3 These studies suggest the potential importance of endothelin in the pathophysiology of hypertension 2 -4 and atherosclerosis.3 Angiotensin I converting enzyme (ACE) inhibitors generally have been used as antihypertensive drugs. However, the precise mechanism of the antihypertensive effects of ACE inhibitors has not been fully elucidated. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0
2

Year Published

1996
1996
2005
2005

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 20 publications
5
32
0
2
Order By: Relevance
“…Although several studies have demonstrated circulating ET activation in experimental and human CHF, the pathophysiologic significance of this elevation remains unclear. However, recent studies in a model of acute renal dysfunction and ET activation during ET A receptor blockade suggested a role for ET in the regulation of acute systemic and renal hemodynamics (31). The present study extends those observations to a state of chronic ET activation and marked vasoconstriction and reports an important role for endogenous ET in the maintenance of arterial pressure and in the regulation of SVR in this state of a chronically reduced CO.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Although several studies have demonstrated circulating ET activation in experimental and human CHF, the pathophysiologic significance of this elevation remains unclear. However, recent studies in a model of acute renal dysfunction and ET activation during ET A receptor blockade suggested a role for ET in the regulation of acute systemic and renal hemodynamics (31). The present study extends those observations to a state of chronic ET activation and marked vasoconstriction and reports an important role for endogenous ET in the maintenance of arterial pressure and in the regulation of SVR in this state of a chronically reduced CO.…”
Section: Discussionsupporting
confidence: 79%
“…This mechanism is supported by our studies in group II in which chronic ACE-I abolished the increases in both the circulating and tissue ET in this model and by the plasma AII concentrations which decreased to levels no different than in normal animals in the presence of chronic ACE-I. However, this observation should be interpreted with caution since other mechanisms other than AII inhibition may be involved, including the potentiation of bradykinin which via nitric oxide and cGMP could also suppress ET production as suggested by recent studies in cultured endothelial cells (31,32). Nevertheless, modulation of circulating and tissue ET may play an important role in the therapeutic actions of ACE-I agents which are commonly used in patients with heart failure.…”
Section: Discussionsupporting
confidence: 47%
“…However, ET-1 excretion was only partially reduced by ACE inhibition, thus indicating that renal ET-1-forming activity was largely independent of the renin-angiotensin system. Moreover, the increased kinin activity that occurs during ACE inhibition (2) might directly inhibit ET-1 renal production, because previous studies showed that bradykinin inhibited ET-1 production from cultured endothelial cells (18).…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin augments ET-1 secretion and ET-1 stimulates the conversion of angiotensin I to angiotensin II. 42,43 Angiotensin-converting enzyme inhibitors block these effects and attenuate ET-1 production in vivo. 44 Possible mechanisms for the preservation of endothelial function by chronic endothelin receptor antagonists include many of the same mechanisms as those suggested for chronic angiotensin-converting enzyme inhibitors, including augmentation of nitric oxide.…”
Section: Best Et Al April 6 1999mentioning
confidence: 99%